Effects of bypass diode configurations to the maximum power of photovoltaic module - Teo J.C.; Tan R.H.G.; Mok V.H.; Ramachandaramurthy V.K.; Tan C.K. (Engineering and Technology Publishing, 2023)
Effects of bypass diode configurations to the maximum power of photovoltaic module are presented. The impacts of one, two and three bypass diodes configurations to the photovoltaic module are investigated using simulation approach. Simulink models are developed to perform all the simulations in this investigation. In the investigation, various shading patterns are applied to one, two and three bypass diodes configurations to investigate the impact of bypass diode configuration to the maximum power of photovoltaic module. Simulation results show that the bypass diode configurations doesnt affect the maximum power of the photovoltaic module under certain shading conditions. The comparison study among one, two and three bypass diodes configurations show a greater quantity of bypass diode in a photovoltaic module doesnt guarantee better performance during partial shading conditions. 2017, Engineering and Technology Publishing. All rights reserved.